RNA Splicing: A Versatile Regulatory Mechanism in Pediatric Liver Diseases - Zhou, Jian-Li; Zhao, Yu-Zhen; Wang, Shan-Shan; Chen, Mo-Xian; Zhou, Shaoming; Chen, Chen (Frontiers in Molecular Biosciences, 2021)
With the development of high-throughput sequencing technology, the posttranscriptional mechanism of alternative splicing is becoming better understood. From decades of studies, alternative splicing has been shown to occur in multiple tissues, including the brain, heart, testis, skeletal muscle and liver. This regulatory mechanism plays an important role in physiological functions in most liver diseases. Currently, due to the absence of symptoms, chronic paediatric liver diseases have a significant impact on public health. Furthermore, the progression of disease is accelerated in children, leading to severe damage to their liver tissue if no precautions are taken. To this end, this review article summarizes the current knowledge of alternative splicing in paediatric liver diseases, paying special attention to liver damage in the child stage. The discussion of the regulatory role of splicing in liver diseases and its potential as a new therapeutic target is also included.